(untitled) (Revista de Estudos Sociais, 2019)
The per capita primary energy consumption-economic growth nexus is examined in a panel of oil-producing countries over a long period (1970-2015), controlling for the exports of goods and services, the ratio of oil production to oil consumption, the oil rents, and international crude oil prices. It is confirmed that these countries share common spatial patterns, unobserved common factors, or both. A dynamic Driscoll-Kraay estimator, with fixed effects, is used to cope with the heteroskedasticity, contemporaneous correlation, first-order autocorrelation, and cross-sectional dependence. Results prove that energy consumption drives economic growth, but only on the short-run. The ratio of oil production to oil consumption has exerted a positive impact on growth in both the short- and long-run. Oil prices only exert a positive effect on growth in the short-run. Oil rents depress growth, suggesting that oil is more a curse than a blessing for the economies.